Control of dendritic cell trafficking in lymphatics by chemokines - Johnson, L; Jackson, D (Kluwer Academic Publishers, 2014)
Dendritic cells (DCs) are crucial participants in maintaining immune surveillance of the periphery and initiating primary immune responses within the draining lymph nodes. The afferent lymphatic vessels provide a conduit for this essential trafficking and, as this review will describe, play an active role in regulating DC migration. Afferent lymphatic capillaries support constitutive trafficking of DCs from resting, non-inflamed tissue, to maintain tolerance against self-antigen and to provide immune surveillance. Following exposure to pathogens or pro-inflammatory cytokines, DCs mature from phagocytes to professional antigen-presenting cells, whilst the lymphatic endothelium adopts an activated phenotype to support the ensuing increase in leukocyte trafficking. The lymphatic endothelial-derived chemokine CCL21 plays a well-characterized role in directing migration of CCR7+ DC in both resting and acute inflammatory conditions. However, efficient trafficking of DCs from inflamed tissue also demands additional chemokine-receptor pairs. Thus, entry of DCs to activated lymphatic vessels is an intricately regulated multi-step process involving numerous chemokines and adhesion molecules. © 2013 Springer Science+Business Media Dordrecht.